Histopathologic Findings of Olfactory Mucosa in COVID-19 Patients - Ghorbani, Jahangir; Pourabdollah, Mahin; Raad, Nasim; Karimi Galougahi, Mahboobeh; Abedini, Atefeh; Farzanegan, Behrooz; Hashemian, Seyed Mohammadreza; Nadji, Seyed Alireza; Safavi Naini, Amirali; Safavi Naini, Ali (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Olfactory manifestations are common findings during the course of COVID-19, while exact physiopathology is not known Aim: We review histological changes of the nasal olfactory mucosa in COVID-19 non-survivors who died in the ICU. Methods: Sampling was done within 1 hour of death under direct vision. Specimens were taken medial to the middle turbinate in the cribriform area and embedded in paraffin blocks and stained by haematoxylin and eosin. Results: The most frequent histologic finding was the infiltration of inflammatory cells mostly comprised of lymphocytes. Inflammatory infiltration of mucosa was seen in all 11 patients with ulceration in 9 cases and neuritis in 3 cases. Conclusion: Inflammatory infiltration of olfactory mucosa may be associated with smell manifestations. Further histological studies will clarify the role of the nasal mucosa in the physiopathology of COVID-19 especially olfactory involvement.